(untitled) - Santrock, John W. (Dubuque, Iowa, 1994)
This learning goals-driven textbook, designed for a topically organized child development course, includes: the largest number of 21st century citations of any text on the market, a student focused learning system integrated throughout, and thoroughly integrated coverage of culture, ethnicity and gender.
Keywords: Child development